PHOTOTHERAPY FOR JAUNDICE - Mesquita, Yasmin Pires dos Santos; Farias, Thayssa Gomes; Dantas, Flávio José da Silva; da Fonseca, Adenilson de Souza (Seven Editora, 2026)
Neonatal jaundice, resulting from hyperbilirubinemia, is one of the most frequent clinical conditions in the postnatal period, affecting approximately 60% of full-term newborns and 80% of preterm infants. This text discusses the pathophysiology and treatment of jaundice through blue light phototherapy, the gold standard for preventing neurotoxicity induced by the accumulation of indirect bilirubin. The pathology is based on the imbalance between the exacerbated production of bilirubin, due to the higher neonatal erythrocyte mass, and the limited hepatic conjugation capacity of the UGT1A1 enzyme, which presents only 1% of adult activity in the first days of life. The therapeutic mechanism of blue light (with peak efficacy between 460 and 490 nm) is based on photochemical processes occurring in the epidermis, transforming liposoluble bilirubin into water-soluble isomers. Among the reactions, structural isomerization is the most relevant, resulting in the formation of lumirrubin, a stable molecule that allows for urinary and biliary excretion without the need for hepatic conjugation. Timely intervention is crucial to prevent the progression of acute bilirubin encephalopathy to kernicterus, a condition characterized by permanent neurological damage. It is concluded that understanding the biophysical mechanisms of phototherapy and rigorous epidemiological monitoring are fundamental for neonatal neurological safety and the reduction of morbidity and mortality associated with hyperbilirubinemia.